Some haematological parameters in sheep infested with coenurus cerebralis and oestrus ovis - Nurcan Dönmez; Uğur Uslu; Banu Atalay (Eurasian Journal of Veterinary Sciences)
This study was conducted to determine somo haematological parameters of sheep infested with C. cerebralis and O. ovis. In the study, 10 sheep as control, 10 sheep infested with C.cerebralis and 10 sheep infested with O. ovis were used. In blood samples taken from all groups, erythrocyte and leukocyte counts, haemoglobine levels, haematocrit value, sedimentation rate, erythrocyte indexes and differential leucocyte counts were determined. Leucocyte count, monocytes percent and sedimentation rate were significiantly higher in coenurosis group than control group's levels. There is no difference between groups in erythrocyte, haemoglobine, haematocrit, MCV, MCH and MCHC levels. The sedimentation rate and monocyte percent were significiantly higher in O. ovis infested group than control. The other parameters were similar in two groups and in normal range for healthy sheep.